Geosemiotics of Linguistic Landscape in the Video Game Honkai: Star Rail - Aushaf Farhan, Andri; Khristianto (Journey: Journal of English Language and Pedagogy, 2026)
Linguistic Landscape is a field of study that focuses on the analysis of signs and its relation to the surrounding environment. Most recent studies concerning linguistic landscapes delve into bilingualism and power relations embedded in each sign. This study employs the theoretical framework of Linguistic Landscape and applies it to analyse the virtual world of the video game Honkai: Star Rail using the Geosemiotics framework. The data of this research was collected from 15th October 2024 to 25th November 2024 during the game’s version 2.7, analysed using a qualitative case study method, and gathered through in-game screenshots. The findings revealed that the signs inside the game used neography and thus must be transliterated into the Roman alphabet. The data showed that each planet’s different theme matches the signs found in-game. Although the signs were deliberately made unreadable to the average player base, their aesthetics, layout, and wording reflect that planet’s story and societal dynamics. These signs improve player immersion and offer insight into developer intent.